Pemberantasan Sarang Nyamuk 3M Plus Sebagai Upaya Preventif Demam Berdarah Dengue Di Desa Labuhan Sumbawa Kecamatan Labuhan Sumbawa - Hamid, Abdul; Hamdin Hamdin; Putri Adekayanti (Ekspresi : Publikasi Kegiatan Pengabdian Indonesia, 2025)
Efforts to control Dengue Hemorrhagic Fever (DHF) through breaking the chain of DHF transmission, namely preventing Aedes aegypti mosquito bites. This community activity aims to control and prevent DHF through Mosquito Nest Eradication (PSN) 3M Plus. DHF is still increasing and is a health dilemma. Lack of public enlightenment on preventing DHF through PSN 3M Plus activities is the cause of DHF continuing to increase every year. This Community Service activity was carried out using the Rapid Action method which was followed by the Community and the Family Empowerment and Welfare Group (TIM PKK) of Labuhan Sumbawa Village, Labuhan Badas District along with students of the Public Health Undergraduate Study Program in accelerating the optimization of the implementation of PSN 3M Plus which was carried out on Friday, January 10, 2025. It is hoped that there will be ongoing intervention related to the implementation of PSN 3M Plus in order to continuously strive for the active participation of the community and (TIM PKK) of Labuhan Sumbawa Village, Labuhan Badas District in carrying out PSN 3M Plus independently, especially in the 1 house 1 mosquito larvae movement. The community needs to be reminded of the importance of PSN 3M Plus which is easy, cheap, safe, and effective